Animasi Interaktif Kesenian Dan Kebudayaan Jawa Barat Untuk Sekolah Dasar - Dewi, Linda Sari; Arisawati, Ester; Sihombing, Erene Gernaria (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2017)
Multimedia aims to present information in the form of a fun, exciting, easy to understand and clear. Then by using interactive animation application as an information medium, Indonesian culture can be delivered using an easy and attractive way. Interactive multimedia learning model is very effective. This can be seen because of the many animated elements. This interactive multimedia learning model will make students do not get bored because students will feel how to play and learn with students will be quicker to capture in the learning takes place, especially to get to know art and culture in western Java. In this interactive animation applications also can increase children's knowledge in order to know more about art and culture located in western Java. In this application contains information cultural arts western Java will students can increase the pride and love of the homeland Indonesia